2012
DOI: 10.1177/070674371205700903
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Psychopathology of Perinatal Depression: Implications for Psychosocial Treatment Development and Delivery in Pregnancy

Abstract: Taking a developmental psychopathology perspective, our objective was to identify ways in which psychosocial treatment of depression during pregnancy may be enhanced. We first consider the state of evidence on psychosocial interventions for antenatal depression, next define key developmental psychopathology concepts that are relevant to antenatal depression, and finally discuss implications for clinical practice and research. We found a limited, but promising, evidence base for effective psychosocial intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
0
18
0
2
Order By: Relevance
“…Consistent with contemporary symptom-based, dimensional approaches to the study of psychiatric disorders (Cuthbert & Insel, 2013), a developmental psychopathology perspective recognizes that psychopathology occurs on a continuum and that contextual factors are critical in defining boundaries between adaptive and maladaptive development along this continuum. For example, somatic symptoms related to sleep, energy, weight, and appetite that are characteristic of psychopathological conditions in non-perinatal phases can result from normative physiological processes of pregnancy and postpartum (Bernstein et al, 2008;Goodman & Dimidjian, 2012;Howard et al, 2014;Matthey & Ross-Hamid, 2011;Misri et al, 2015;Nylen, Williamson, O'Hara, Watson, & Engeldinger, 2013) and may not necessarily indicate psychopathology. Relatedly, symptoms such as heightened anxiety or preoccupation regarding the infant may be a normative feature of new motherhood and represent a healthy maternal response to the infant initially, promoting vigilance, threat detection, and harm avoidance (Leckman et al, 1999(Leckman et al, , 2004Wisner et al, 1999).…”
Section: Maternal Programming: Implications For Psychopathologymentioning
confidence: 99%
“…Consistent with contemporary symptom-based, dimensional approaches to the study of psychiatric disorders (Cuthbert & Insel, 2013), a developmental psychopathology perspective recognizes that psychopathology occurs on a continuum and that contextual factors are critical in defining boundaries between adaptive and maladaptive development along this continuum. For example, somatic symptoms related to sleep, energy, weight, and appetite that are characteristic of psychopathological conditions in non-perinatal phases can result from normative physiological processes of pregnancy and postpartum (Bernstein et al, 2008;Goodman & Dimidjian, 2012;Howard et al, 2014;Matthey & Ross-Hamid, 2011;Misri et al, 2015;Nylen, Williamson, O'Hara, Watson, & Engeldinger, 2013) and may not necessarily indicate psychopathology. Relatedly, symptoms such as heightened anxiety or preoccupation regarding the infant may be a normative feature of new motherhood and represent a healthy maternal response to the infant initially, promoting vigilance, threat detection, and harm avoidance (Leckman et al, 1999(Leckman et al, , 2004Wisner et al, 1999).…”
Section: Maternal Programming: Implications For Psychopathologymentioning
confidence: 99%
“…Among various factors which explain the association of MDSs and adverse outcomes in infancy (e.g., genetic transmission, learning depressive symptoms from depressive mothers, prenatal in utero exposure, attachment, and impaired parenting) (for extensive review, see Goodman & Dimidjian, 2012), research has consistently demonstrated that depressed mothers have difficulties in parenting, especially when they interact with their infants (Dawson et al, 1999;Elgar, Mills, McGrath, Waschbusch, & Brownridge, 2007;Field, 2010;Field et al, 1988;Lovejoy, Graczyk, O'Hare, & Neuman, 2000;Pearson et al, 2012;Tronick & Reck, 2009). Depressed mothers, in comparison to nondepressed mothers, are known to be less likely to have sensitive and responsive interactions with their infants that produce suboptimal developmental outcomes of infants (Reck et al, 2004;Field et al, 2007).…”
Section: Mds and Mothers' Social Interactionsmentioning
confidence: 99%
“…There has been consensus among researchers that maternal depressive symptoms (MDSs) are a risk factor for a number of developmental delays and problems in infancy and childhood (Beardslee, Versage, & Gladstone, ; Campbell, Cohn, & Meyers, ; Field, , , ; Goodman & Dimidjian, ; Murray & Cooper, ; Tronick & Reck, ). Many empirical findings have suggested that mothers’ social interactions with their infants and children have played a mediating role in the link between MDSs and outcomes of infants and children (Goodman & Gotlib, , ; Pearson et al., ; Tronick & Reck, ).…”
mentioning
confidence: 99%
“…Antenatal care enables early detection and treatment of adverse physical 6 and mental health 7 pregnancy related outcomes. The improved data completeness post 2006 demonstrates achievable benefits from well‐founded modification to existing information collection forms.…”
Section: Completeness Of Antenatal Care Information Based On Confinemmentioning
confidence: 99%